2015
DOI: 10.1002/2015ms000531
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing DYNAMO convection with weak temperature gradient simulations

Abstract: Determining relationships between convective and environmental diagnostics can improve our understanding of mechanisms controlling tropical convection, and consequently, result in better representations of convection in coarsely resolved models. We identify important diagnostic relationships in observations taken during the Dynamics of the Madden-Julian Oscillation (DYNAMO) campaign and perform weak temperature gradient (WTG) simulations of DYNAMO convection to determine if the observed relationships are repro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(54 citation statements)
references
References 52 publications
3
47
0
Order By: Relevance
“…Using the same WTG scheme, Sentić et al . [] demonstrate that the evolution of precipitation, lapse rate, and humidity during DYNAMO are well‐represented by the WTG framework. Comparison between measured vertical motion ( w dynamo ) and WTG‐balanced vertical motion from DYNAMO during SP/MJO2 (i.e., w balanced ) further supports that WTG is a reasonable approximation for this period (Figure ) ( wbalanced=Q1(dθ¯/dz)1, where Q 1 is the apparent heat source for SP/MJO2, and the overline indicates a horizontal domain average) (the profile from the control simulation, w ctl , is discussed in more detail later).…”
Section: Experiments and Analysis Methodologymentioning
confidence: 99%
“…Using the same WTG scheme, Sentić et al . [] demonstrate that the evolution of precipitation, lapse rate, and humidity during DYNAMO are well‐represented by the WTG framework. Comparison between measured vertical motion ( w dynamo ) and WTG‐balanced vertical motion from DYNAMO during SP/MJO2 (i.e., w balanced ) further supports that WTG is a reasonable approximation for this period (Figure ) ( wbalanced=Q1(dθ¯/dz)1, where Q 1 is the apparent heat source for SP/MJO2, and the overline indicates a horizontal domain average) (the profile from the control simulation, w ctl , is discussed in more detail later).…”
Section: Experiments and Analysis Methodologymentioning
confidence: 99%
“…The time scale over which the domain mean potential temperature is relaxed to the reference profile ( t θ in equation ) represents the time scale over which gravity waves counteract buoyancy anomalies induced by convective heating. Typical values in WTG investigations are on the order of an hour [ Sessions et al ., ; Wang and Sobel , ; Daleu et al ., ; Anber et al ., ; Wang et al ., ; Sentić et al ., ], though some studies have used strict enforcement ( tθ=0) [ Sobel and Bretherton , ]. We choose a relaxation time scale of approximately 11 min ( 1/tθ=1.5×103 s −1 ).…”
Section: Numerical Experimentsmentioning
confidence: 99%
“…WTG simulations have been used successfully to investigate various properties of convection and convective organization. For example, it has been implemented in a simple model of the Hadley circulation [ Polvani and Sobel , ], the Madden‐Julian Oscillation [ Wang et al ., ; Sentić et al ., ], and cyclogenesis [ Raymond and Sessions , ].…”
Section: Introductionmentioning
confidence: 99%
“…For the same MJO events, Sentic et al . [] also performed numerical simulations using the SWTG method and found that their simulations were capable of reproducing important relations between convection and large‐scale environment—including atmospheric stability, moisture, and gross moist stability.…”
Section: Introductionmentioning
confidence: 99%